Age-related Hearing Loss Is Strongly Associated With Cognitive Decline Regardless of the APOE4 Polymorphism. Issue 10 (December 2019) - Morita, Yuka; Sasaki, Takanobu; Takahashi, Kuniyuki; Kitazawa, Meiko; Nonomura, Yoriko; Yagi, Chihiro; Yamagishi, Tatsuya; Ohshima, Shinsuke; Izumi, Shuji; Wakasugi, Minako; Yokoseki, Akio; Narita, Ichiei; et al.
Abstract : Objective: To examine the association between hearing impairment and cognitive decline and to identify possible risk factors for presbycusis. Study Design: Cross-sectional survey in prospective cohort study. Setting: University hospital. Patients: A total of 322 participants aged >60 years, for whom all the below data were available, were enrolled in the study. There were 168 females and 154 males with a median age of 71 years (range: 60–89 yrs). Interventions: PROST (Project in Sado for Total Health), a medical database in Sado island Japan, was analyzed. Main Outcome Measures: Data on pure-tone audiometry, mini-mental state examination (MMSE), polymorphism of apolipoprotein E4 (ApoE4), diabetes mellitus, hypertension, smoking, and alcohol consumption were extracted. Hearing impairment was defined as an average frequency between 0.25 and 8 kHz that exceeded 30 dB. Multivariate analysis was used to identify which of the above factors could predict the hearing impairment. Hearing threshold of each Hz was compared between the ApoE4 (+/+), (+/−), and (−/−) groups. Results: Among various factors, only low MMSE scores (<24) showed significant association with hearing impairment. There were no differences in the hearing threshold of all frequencies between ApoE status groups. Conclusions: Hearing impairment was associated with low MMSE sores, regardless of the ApoE4 status. If ApoE4 status would be a common upstream predictor for both the hearing and cognitive impairment, hearing threshold would be related to ApoE4 status. However, these results may suggest that hearing impairment may be causally related to the cognitive dysfunction, perhaps via the cognitive load mechanisms.